Travel Victoria / Harith Akmal Jamali... [et al.] - Majid, Idris; Rahmat, Muhd. Nur Hafiqh; Mohamad, Nurhafiza; S. Ramitan, Mischeell Chandron; Abd Isa, Nurazirah; Jamali, Harith Akmal (2016)
Our business is registered by the name of Travel Victoria. The words "Victoria" from the old name of that island because WP Labuan once called Victoria at British invasion era.